Human umbilical cord mesenchymal stem cells regulate immunoglobulin a secretion and remodel the diversification of intestinal microbiota to improve colitis - Liu, Airu; Wang, Xing; Liang, Xiaonan; Wang, Wenxin; Li, Chenyang; Qian, Jiaming; Zhang, Xiaolan (Frontiers in Cellular and Infection Microbiology, 2022)
Background. Mesenchymal stem cells (MSCs) therapy has emerged as a promising novel therapeutic strategy for managing inflammatory bowel disease (IBD) mainly via dampening inflammation, regulating immune disorders, and promoting mucosal tissue repair. However, in the process, the associated changes in the gut microbiota and the underlying mechanism are not yet clear. Methods. In the present study, dextran sulfate sodium (DSS) was used to induce colitis in mice. Mice with colitis were treated with intraperitoneal infusions of MSCs from human umbilical cord (HUMSCs) and evaluated for severity of inflammation containing weight reduction, diarrhea, bloody stools, histopathology and mortality. The proportion of regulatory T cells (Tregs) and immunoglobulin A positive (lgA+) plasmacytes in gut-associated lymphoid tissue (GALT) were determined. The levels of IgA from intestinal and feces were tested. And the proportion of IgA-coated bacteria was also determined. Fecal microbiome was analyzed using 16S rRNA gene sequencing analyses. Results. Treatment with HUMSCs ameliorated the clinical abnormalities and histopathologic severity of acute colitis in mice. Furthermore, the proportion of Tregs in Peyer’s patches (PPs) and lamina propria of small intestine (sLP) was both significantly increased, and meanwhile the proportion of lgA+ plasmacytes was also substantially higher in MSCs group than that of DSS group, resulting in elevated levels of lgA from intestinal and feces. And the proportion of IgA-coated bacteria was also up-regulated in MSCs group. In addition, the microbiome alterations in mice with colitis were partially restored to resemble those of healthy mice following treatment with HUMSCs. Conclusions. Therapeutically administered HUMSCs ameliorates DSS-induced colitis partially via regulating Tregs-lgA response, promoting the secretion of lgA and furtherly facilitating the restoration of intestinal microbiota, which provides a potential therapeutic mechanism for HUMSCs in the treatment of IBD.